Variation between the copula si "to be" and the l-clitics in Romani spoken in Mexico. Issue 2 (December 2018) - Padure, Cristian; De Pascale, Stefano; Adamou, Evangelia
Abstract : This research aims to investigate the innovative use of the subject clitic pronouns lo, la, le in attributive predications, e.g. O xabe lašo lo " The dinner is good, " in Romani spoken in the State of Veracruz, Mexico. The analysis of a 15-hour conversational corpus in Romani shows that the Romani copula si is used in variation with the subject clitic pronouns in l - in third person, affirmative clauses. In addition, 60 Romani-Spanish bilinguals from Veracruz responded to a contextualized copula choice task. Generalized linear mixed effect models were constructed to analyse the results. The analysis shows that the clitics are extremely dynamic in third person affirmative sentences and further reveals the linguistic variables that determine their use.